PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF MATERI â€œPENGARUH SOSIAL BUDAYA TERHADAP SIKAP BERAGAMA UMAT ISLAM INDONESIAâ€ - Yiyin Isgandi (MUADDIB Jurnal Kependidikan dan Keislaman, 2020)
This research and development aims to produce interactive multimedia learning material â€œThe influence of socio-culture on the religious attitudes of Indonesian Muslimsâ€ for college student. This study uses the 4D Thiagarajan et al model with Adobe Flash Professional CS3 software. Validation was carried out by two teams of material experts and multimedia experts, and was tested on a limited and wider basis on fifty students. Validated aspects are the appropriateness of the content, language, presentation, content display, and presentation characteristics. The assessment results from the material expert got an average score of 4 with the â€œGoodâ€ catagory, from multimedia experts got score 3,86 with the â€œGoodâ€ catagory. This product also received a response by collage student and got an average score 3,83 with the â€œGoodâ€ catagory. Based on the pre-determined eligibility qualifications of 2,60-5, it can be concluded that this learning multimedia is feasible and ready to be implemented in learning Islamic Education at STKIP Al Hikmah Surabaya.